2008
DOI: 10.2460/ajvr.69.11.1406
|View full text |Cite
|
Sign up to set email alerts
|

In vitro mechanical evaluation of medial plating for pantarsal arthrodesis in dogs

Abstract: Because of lower peak strains, the MAP2 may be less susceptible to failure than the MAP1. Furthermore, CTS augmentation was unnecessary with MAP2s, which could minimize intra- and postoperative morbidity. Compared with what is known for dorsal plates, MAP2 constructs were associated with approximately 35% less AD. As a result of improved local stability, one might anticipate earlier fusion of the talocrural joint with an MAP2. In addition, plate peak strain was approximately 3.5 times lower in MAP2s than in do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Lastly, alternative plate locations may influence the bending resistance of PCA constructs. With medial plates, the plate is bent on edge, which significantly increases the plate AMI during bending within the sagittal plane (20). Similarly, with palmar plates, bending moments acting on the construct should be converted into tensile forces within the plate (12).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, alternative plate locations may influence the bending resistance of PCA constructs. With medial plates, the plate is bent on edge, which significantly increases the plate AMI during bending within the sagittal plane (20). Similarly, with palmar plates, bending moments acting on the construct should be converted into tensile forces within the plate (12).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by results from an ex vivo study that provided evidence that placement of a calcaneotibial screw significantly reduces compliance, angular deformity, and strain of medial arthrodesis plates. 13 For these reasons, we adopted it in most procedures. Additional studies are required to investigate the effect of additional internal fixation on outcome and complications of PTA by medial plate fixation and also to quantitate the effect of different types of additional internal fixation on overall construct stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…This ex vivo finding would appear to be supported by the results of a retrospective study on PCA in which it was concluded that external coaptation had no measurable benefit . From a mechanical perspective in PTA, medial plating allows “edge” loading of the implant, and, compared to dorsal plating, increases the dorsoplantar bending stiffness of the construct . Furthermore, the distal screws engage multiple metatarsal bones due to their mediolateral orientation offering a theoretical mechanical advantage compared to dorsal plating.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors of this study are to be commended for producing a study focused on complications, because it provokes us to think about why these complications occur and what can be done to reduce their occurrence and severity. One approach to this problem is to develop more secure implants for tarsal and carpal arthrodesis, such as reinforced pantarsal arthrodesis plates, plate-pin combinations and broad cast-less arthrodesis plates, so that external coaptation is not needed (2,3). In the same vein, the reconstruction of calcaneal tendon injury can be protected with a tibio-calcaneal screw or circular external fixator, so that additional external coaptation can be avoided (4).…”
mentioning
confidence: 99%